The Role of Sustainability Reports, Earnings Quality, And Company Size In Determining Company Value - Kusuma Dewi; Annisa Kamilani; Tri Marlina; Triandi Triandi (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study examines the influence of sustainability reporting, earnings quality, and firm size on firm value among companies consistently listed in the SRI-KEHATI Index during the 2020–2024 period. The decline in firm value as measured by Tobin’s Q and the downward trend in earnings quality among sustainable companies raise questions about the effectiveness of sustainability practices and financial performance in enhancing market perception. This research aims to empirically analyze how the extent of sustainability report disclosure, earnings quality based on the ratio of operating cash flow to earnings, and firm size affect firm value. The study employs a quantitative approach using balanced panel data consisting of 59 observations, analyzed through multiple linear regression and classical assumption testing using SPSS. The results reveal that sustainability reporting has a significant negative effect on firm value, indicating that sustainability disclosures have yet to be perceived as positive signals by investors. Earnings quality also shows a significant negative effect, suggesting potential earnings management practices and investor skepticism toward reported financial information. Conversely, firm size significantly and positively influences firm value, reaffirming that larger firms are more capable of convincing the market regarding their stability and growth prospects. Collectively, the three variables explain 30.3% of variations in firm value. These findings conclude that sustainability reporting and earnings quality are not yet the primary determinants of firm value among sustainable firms in Indonesia, while firm size remains the most influential factor for investors. Keywords: sustainability reporting; earnings quality; firm size; firm value; SRI-KEHATI